TOTAL QUALITY MANAGEMENT TERHADAP KINERJA MANAJERIAL DENGAN SISTEM PENGUKURAN KINERJA SEBAGAIVARIABEL MODERATING PADA FAJAR GRUP - Wawan Darmawan (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2017)
Total Quality Management (TQM) is one technique that is often used by companies in order to improve its performance.The aims of the research were to (1) determine and test whether total quality management (TQM)has positive effect on managerial performance at Fajar Group, (2) determine and test whether TQM measurement has effect on managerial performance at Fajar Group, (3) determine and test whether measurement system of TQM has a role as moderating variable between TQM and managerial performance at Fajar Group. The research was a quantitative study conducted in companies belonging to Fajar Group. The population consisted of 58 respondents taken from 24 companies by considering the number of managers at mid-level of each company . The measurement wasdone using quantitative data with Moderated Regression Analysis (MRA) analysis. The results of the research indicate that (1) TQM has positive effect on managerial performance, (2) performance measurement system has positive effect on managerial performance at Fajar Group, (3) TQM interaction with performance management system has effect on managerial performance at Fajar Group.Keyword: total quality management, managerial performance.